2021
DOI: 10.3390/geriatrics6010008
|View full text |Cite
|
Sign up to set email alerts
|

Knee Extension Strength Measures Indicating Probable Sarcopenia Is Associated with Health-Related Outcomes and a Strong Predictor of 1-Year Mortality in Patients Following Hip Fracture Surgery

Abstract: To examine if knee-extension strength (KES) measures indicating probable sarcopenia are associated with health-related outcomes and if KES and hand grip strength (HGS) measures are associated with 1-year mortality after hip fracture. Two groups of older patients with hip fracture had either HGS (n = 32) or KES (n = 150) assessed during their acute hospital stay. Cut-points for HGS (<27 kg for men and <16 kg for women), and cut-points for maximal isometric KES (non-fractured limb), being the lowest sex-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Clinicians are exempted from actively exploring potential causes, especially reversible ones, and providing appropriate personalized intervention countermeasures for older people with possible sarcopenia (Chen L. K. et al, 2020 ). Current studies have also suggested that possible sarcopenia is associated with decreased physical function (Kristensen et al, 2021 ; Lim and Kong, 2022 ) and increased risks of cognitive impairment (Maeda and Akagi, 2017 ; Cipolli et al, 2021 ), stroke (6), and 1-year mortality (Kristensen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians are exempted from actively exploring potential causes, especially reversible ones, and providing appropriate personalized intervention countermeasures for older people with possible sarcopenia (Chen L. K. et al, 2020 ). Current studies have also suggested that possible sarcopenia is associated with decreased physical function (Kristensen et al, 2021 ; Lim and Kong, 2022 ) and increased risks of cognitive impairment (Maeda and Akagi, 2017 ; Cipolli et al, 2021 ), stroke (6), and 1-year mortality (Kristensen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, even the fitter hip fracture patients have strength deficits and potential for improving strength and function. In a recently published study, we found that almost half of hip fracture patients were classified as probable sarcopenic using cut-points for knee extension strength of the nonfractured leg and hand grip strength [49]. Furthermore, a study by Dyer et al [7] showed that among the fitter patients, only 40-44% recovered their prefracture mobility independence.…”
Section: Strength and Limitsmentioning
confidence: 92%
“…All patients were given a minimum of 3 trials (a 4th and 5th trial were given if the 3rd and 4th, respectively, exceeded the previous result) using the dominant hand. All values were documented in kilograms and the highest was used for analysis [18] .…”
Section: Hand Grip Strengthmentioning
confidence: 99%